In vitro Assessment of the Antimicrobial Potential of Some Commercial Herbal Products - Zahraa Hashim (University of Mosul, 2022)
Natural plant products have been widely used as an alternative approach to treat microbial infections to overcome issues of antibiotics-associated side effects and the emergence of resistant pathogens. One of the most popular infections causing significant morbidity and death toll is urinary tract infection. This study is designed to evaluate the antimicrobial and antibiofilm potential of four commercial herbal products against five uropathogenic clinical isolates. In vitro, well diffusion assay and crystal violet staining techniques were used to evaluate the antimicrobial and antibiofilm effects respectively. Antimicrobial effect was reported for Renalka™ against Enterococcus faecium, ROWAtinex® against Staphylococcus aureus and E. faecium and UROCLEAR against Candida albicans. A significant antibiofilm effect, semi-quantified by stained biomass, was reported for all of the products included in the study against the tested pathogens but to a varying degree. Medicinal herbal products can exert a substantial prophylactic antibiofilm effect in addition to their beneficial health effects in treating urological pathologies.